2021
DOI: 10.1631/jzus.a2000316
|View full text |Cite
|
Sign up to set email alerts
|

Damage detection in steel plates using feed-forward neural network coupled with hybrid particle swarm optimization and gravitational search algorithm

Abstract: Over recent decades, the artificial neural networks (ANNs) have been applied as an effective approach for detecting damage in construction materials. However, to achieve a superior result of defect identification, they have to overcome some shortcomings, for instance slow convergence or stagnancy in local minima. Therefore, optimization algorithms with a global search ability are used to enhance ANNs, i.e. to increase the rate of convergence and to reach a global minimum. This paper introduces a two-stage appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…By incorporating these parameters into the objective function of the metaheuristic algorithm, the algorithm searches for the optimal combination of damage locations and severities that best match the observed vibration data such as Particle Swarm Optimization (PSO) (Gökdağ and Yildiz, 2012;Kang et al, 2012;Nguyen-Ngoc et al, 2021); Teaching Learning Based Optimization (TLBO) (Ahmadi-Nedushan and Fathnejat, 2022;Shahrouzi and Sabzi, 2018); Slime Mould Algorithm (SMA) (Ngoc-Nguyen et al, 2023), Artificial Hummingbird Algorithm (AHA) ; Marine Predator Algorithm (MPA);…Besides, many hybrid metaheuristic algorithms combined with neural networks (Hoàng Việt et al, 2023;Su Fen et al, 2023) have also been applied to fault diagnosis, Feedforward Neural Networks and Marine Predator Algorithm (MPAFNN) (Ho et al, 2021b); Grey Wolf Optimizer and Artificial Neural Networks (GWOANN) (Ho Viet et al, 2022); Particle Swarm Optimization-Gravitational Search Algorithm (PSOGSA); Feedforward Neural Network-Particle Swarm Optimization and Gravitational Search Algorithm (FNN-PSOGSA) (Ho et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating these parameters into the objective function of the metaheuristic algorithm, the algorithm searches for the optimal combination of damage locations and severities that best match the observed vibration data such as Particle Swarm Optimization (PSO) (Gökdağ and Yildiz, 2012;Kang et al, 2012;Nguyen-Ngoc et al, 2021); Teaching Learning Based Optimization (TLBO) (Ahmadi-Nedushan and Fathnejat, 2022;Shahrouzi and Sabzi, 2018); Slime Mould Algorithm (SMA) (Ngoc-Nguyen et al, 2023), Artificial Hummingbird Algorithm (AHA) ; Marine Predator Algorithm (MPA);…Besides, many hybrid metaheuristic algorithms combined with neural networks (Hoàng Việt et al, 2023;Su Fen et al, 2023) have also been applied to fault diagnosis, Feedforward Neural Networks and Marine Predator Algorithm (MPAFNN) (Ho et al, 2021b); Grey Wolf Optimizer and Artificial Neural Networks (GWOANN) (Ho Viet et al, 2022); Particle Swarm Optimization-Gravitational Search Algorithm (PSOGSA); Feedforward Neural Network-Particle Swarm Optimization and Gravitational Search Algorithm (FNN-PSOGSA) (Ho et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is to use a damage index derived from frequencies and/or mode shapes, which can directly indicate damage location without an iterative process [9][10][11][12][13]. These studies share the same assumption that information about the pristine and damaged structure is already achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Although all these mentioned studies, in general, showed high potential in damage localization, they did not indicate a quantitative relationship between the damage indices and the reduction in stiffness. To solve this problem, many authors combined damage indicators with an optimization process [23][24][25][26] or used a hybrid model between optimization and feedforward neural network (FNN) coupled with damage indicator [27,28]. The first approach identifies the damage by solving inverse problems or updating some model parameters until meeting a superior agreement between the FE model and the measured modal parameters.…”
Section: Introductionmentioning
confidence: 99%